Solubility of sulphadiazine in (acetonitrile + water) mixtures: measurement, correlation, thermodynamics and preferential solvation (2019)
The equilibrium solubility at temperatures from (293.15 to 313.15) K, dissolution thermodynamics and preferential solvation of sulphadiazine (SD) in {acetonitrile (ACN) (1) + water (2)} mixtures is reported. Mole fraction solubility of SD (x3) increase